Surface Radiation Balance of Urban Materials and Their Impact on Air Temperature of an Urban Canyon in Lisbon, Portugal - Matias, Márcia (2020)
Urban climate results from the modifications caused by the characteristics of cities, which modifies the regional climatic conditions of a city. When urban areas are warmer than the surrounding areas, the urban heat island (UHI) phenomenon occurs. Being a major phenomenon and a global topic of interest for all affected cities, there are already numerous studies that address this subject. However, most studies are only focused on the macro and mesoscales. This study looks at the micrometeorological scale in a neighborhood of Lisbon (Telheiras). Having as a main objective to evaluate how the radiation balance of urban materials influences air temperature in an urban canyon, thermal images of different urban materials were obtained using infrared thermography, a technique that allowed understanding how the temperatures registered in the facades and other urban surfaces can affect the air temperature of the urban canyon. The components of the radiation budget were obtained by using a pyranometer and a pyrgeometer. Moreover, a microclimatic network to monitor air temperature and relative humidity was installed in the study area. The results show that, when the streets are less exposed to the prevailing wind direction in Lisbon (north and northwest), air temperatures are slightly higher than those found in opposite conditions. Both the temperature and the radiative balance of the facades and other surfaces (asphalt, light Portuguese sidewalk, and tile floor) respond directly to incident solar radiation. As expected, it was found that south facades have the highest temperatures of the four exposures under study (>4 ◦C when compared to the opposite facade), and the highest radiative balance was always registered on asphalt when compared to the sidewalk (at 9:00 a.m. + 30 W·m−2 , at 1:00 p.m. + 149 W·m−2 , and at 7:00 p.m. + 66 W·m−2 ).